EU enlargement and the Portuguese economy - Crespo, N.; Fontoura, M. P.; Barry, F. (The World Economy, 2004)
The main focus of the present paper is on the emerging and likely future trade effects of enlargement. Though our particular concern is with Portugal, we set the scene by comparing the trade structures of the 10 countries of Central and Eastern Europe (i.e. the eight CEE accession states plus Bulgaria and Romania) – including an analysis of the individual cases of the Czech Republic, Hungary and Poland – with those of the EU15 as a whole, and with those of the 4 EU cohesion countries. The elimination of trade barriers between incumbents and accession states will have two trade-related effects on EU incumbents: an increase in bilateral flows with the CEEC and a shift effect as the CEEC displace some incumbent exports to EU markets. The first effect is likely to be strongest for those incumbents for which there is a strong overlap between their export structure and the import structure of the CEEC. Portugal emerges as one of the economies with the least overlap. The displacement effect, we conclude, is likely to be particularly strong in the case of Portugal, given the high degree of similarity between Portuguese exports and those of the CEEC. Portugal appears to be ‘being squeezed from below’ in that, for the majority of its traditional export sectors, the CEEC became progressively more competitive during the second half of the 1990's. Portuguese specialisation was increasingly confined to low-technology, low-added-value sectors with declining demand, as strong FDI inflows to the CEEC led to an increasing preponderance of more dynamic sectors in their export structures. Thus, Portugal is also being squeezed from above. This suggests that there may be substantial industrial disruption, in response to which labour-market flexibility and dynamic entrepreneurial response is crucial. Intersectoral mobility is generally easier the more highly educated the workforce – an indicator on which Portugal scores poorly. The Portuguese labour market, however, displays a high degree of flexibility, consistent with its long lasting low rate of unemployment. Continued flexibility will help minimise these likely adjustment costs. Besides the trade and industry effects, other topics considered in the paper include the implications of enlargement for Portugal's ability to attract FDI, the likely consequences for Portugal of inward migration from the CEEC to the EU, and the implications of enlargement for Portugal's budgetary relations with the rest of the EU.